The Involvement of the Chemokine RANTES in Regulating Luminal Acidification in Rat Epididymis - Feng, Xiao; Ma, Bin-Fang; Liu, Bo; Ding, Peng; Wei, Jin-Hua; Cheng, Pang; Li, Sheng-Yu; Chen, Dong-Xu; Sun, Zhi-Jian; Li, Zhen (Frontiers in Immunology, 2020)
Background: A complex interplay between the different cell types presented in the epithelium leads to activation of the luminal acidifying capacity of the epididymis, a process that is crucial for sperm maturation and storage. Basal cells of epididymal epithelium sense the luminal angiotensin II (ANG II) and stimulate proton secretion in clear cells through nitric oxide (NO). Our previous study has shown the chemokine regulated upon activation normal T-cell expressed and secreted (RANTES) was expressed in the F4/80 positive cells of human epididymis. The objective of this study was to explore the involvement of RANTES in regulating the luminal acidification in the rat epididymis. Methods: The role of RANTES was explored by in vivo perfusion with recombinant RANTES, Met-RANTES, and PBS of different pH values. Furthermore, rat vasectomy was established to alter the epididymal luminal pH. RIA was used to measure the tissue homogenate ANG II concentration. Real time-PCR and western blot were used to detect the expression levels of AGTR2, RANTES, CCR1, CCR5 and iNOS in epididymis. Results: RANTES was restricted to the macrophages of epididymal ducts and co-localized with its receptors CCR1 and CCR5. Both V-ATPase and iNOS were up-regulated in the cauda epididymis after perfusing with recombinant RANTES, while the antagonist Met-RANTES perfusion led to a complete abrogation of the increased expression of V-ATPase on the apical membrane of clear cells and iNOS in macrophages. Upon alkaline perfusion, RANTES expression was signiﬁcantly increased and the apical accumulation of V-ATPase on the clear cells was induced in the cauda epididymis. The luminal pH in the cauda epididymis increased after vasectomy. The concentration of the ANG II and the expression levels of AGTR2, RANTES, CCR1, CCR5 and iNOS were reduced in the cauda epididymis following vasectomy. Conclusion: Activation of AGTR2 in basal cells by luminal ANG II may stimulate RANTES in basal macrophages to induce the production of NO, which increases proton secretion by adjacent clear cells. Thus, RANTES is possible to participate in the crosstalk among basal cells, macrophages and clear cells for the fine control of an optimum acidic luminal environment that is critical for male fertility.